2012
DOI: 10.1039/c2ce25972a
|View full text |Cite
|
Sign up to set email alerts
|

The effect of halogen bonding on the packing of bromine-substituted pyridine and benzyl functionalized resorcinarene tetrapodands in the solid state

Abstract: The synthesis and characterization of new bromine substituted pyridine and benzyl functionalized tetramethoxy resorcinarene tetrapodands are described and their solid state structural properties and interactions were studied by single crystal X-ray crystallography. Three different crystal structures were obtained for the pyridine derivative and one for the benzyl derivative, which revealed that the interactions 10 of the bromine substituent have explicitly an effect on the crystal packing of the resorcinarene … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
7
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 44 publications
2
7
0
Order By: Relevance
“…The boat conformation is defined by two resorcinol rings being almostv ertically oriented and the two remaining ones horizontally aligned. Previously,s elf-inclusion dimers of resorcinarene tetrapodands have been observed by us [31,32] and others. [33][34][35][36] Nevertheless,r esorcinarene podands tend to display collapsed cavities in the solid state.…”
Section: Introductionmentioning
confidence: 76%
“…The boat conformation is defined by two resorcinol rings being almostv ertically oriented and the two remaining ones horizontally aligned. Previously,s elf-inclusion dimers of resorcinarene tetrapodands have been observed by us [31,32] and others. [33][34][35][36] Nevertheless,r esorcinarene podands tend to display collapsed cavities in the solid state.…”
Section: Introductionmentioning
confidence: 76%
“…Since the bond angles around halogen···halogen interactions [C14-Br4···Br4 = 78.95(5)°] are the same, it can be termed as a halogen···halogen interaction of V geometry (Figure 20). Recently similar types of Br···Br interaction in bromine-substituted resorcinarenes have been reported by Nissinen et al 18 Similar to complex 2e, in 2e′ nonclassical H-bonding interactions of C5-H5···Br2-Cu1 = 3.66(1) Å between two nearby monomers result in centrosymmetric molecules as shown in Figure 26. The distance between the two copper centers in nearby molecules interlinked through the above NH···Br H-bonding interactions is 8.615(2) Å and through discrete halogen···halogen interaction is 14.853(3) Å.…”
mentioning
confidence: 62%
“…The same two trends were also seen in earlier structures of pyridine functionalized resorcinarenes. 18,21 In all structures of compounds 1 and 2, regardless of the 3-or 4-position, the pyridine nitrogen atoms point away from the cavity being properly aligned for forming intermolecular interactions.…”
Section: Resultsmentioning
confidence: 99%
“…Only recently, Jungbauer et al 17 reported strong molecular recognition of a finite three-point halogen bonded assembly both in solution and in the solid state, where the receptor/substrate match was nearly perfect when the number of the donor and acceptor sites was equal but less optimal with substrates having fewer acceptor sites than the ideal three. Our earlier study explaining the properties of halogenated resorcinarenes and their solid state packing that was driven by intermolecular halogen bonds 18 intrigued us to explore the potential of tetrapyridine functionalized resorcinarenes in the construction of halogen bonded networks with aryl halides as connecting linkers. Herein, we present the synthesis and solution dynamics of two multidimensional resorcinarene based halogen bond acceptors, as well as, a successful construction of two network structures stabilized by halogen bonds, in which the dimensionality and architecture was obtained by the resorcinarene core, directionality by the podand pyridine arms and cohesion by the aryl halide linkers.…”
Section: 16mentioning
confidence: 99%